PENGARUH INFORMASI AKUNTANSI TERHADAP PENGAMBILAN KEPUTUSAN (ESKALASI KOMITMEN) - Halimatus Sa’diyah; Abdul Wahid Mahsuni; Muhammad Cholid Mawardi (Universitas Islam Malang, 2018)
ABSTRACTThis research is conducted with the purpose of: To know the effect ofaccounting information (Not Ambiguous, Progress and Advantages to theescalation of commitment. Population used in this research are Student of Facultyof Economics & Business of Islamic University of Malang and University ofMuhammadiyah Malang who have taken the course of Accounting InformationSystem. The sample selection in this research is using proportional randomsampling. Based on the criteria used there are 240 respondents who weresampled. The method used in this research is multiple linear regression method.Based on the results of research can be taken some conclusions are: 1) t resultsindicate that unambiguous variables affect the escalation of commitment, 2) thevariable progress affect the escalation of commitment, 3) profit variables affectthe escalation of commitment, and 4) F results indicate that the variableambiguity, progress, and profits affect the escalation of commitment.Keywords: Unambiguous, progress, profit and commitment escalation.